Place-Based Policies in Deprived Neighbourhoods: Opportunities for Preexisting Residents and Neighbourhood Revitalisation? - Anna Piil Damm; Ahmad Hassani; Jonas Søndergaard Sørensen (Institute of Labor Economics (IZA), 2025)
This paper asks whether Denmark's large-scale intervention in disadvantaged public-housing neighbourhoods on the "Ghetto List" in 2010 altered the trajectories of the neighbourhoods and improved economic outcomes of pre-existing residents through infrastructural improvements and social programmes. We leverage a novel geo-referenced data set linked with administrative registers and defines similar, yet untargeted neighbourhoods and their pre-existing residents as the control group. Our difference-in-difference estimates show that the programme reduced crime, both through a short-run compositional change, and through an 9.5% reduction in the likelihood of a criminal conviction among pre-existing residents, driven by those with a history of criminal activity.
Keywords: J6; J24; O15; R23; R28; 330; local community development; economic deprivation; human resources; residential segregation; migration; public policy analysis